TRANSFORMASI RITEL FESYEN MELALUI TEKNOLOGI & DATA - Susi Hartanto (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2022)
Omnilytics is a technology and data-based fashion market insight provider that power decision making through a complete view of market demand, such as: 1) Competitor benchmarking, 2) Trend performance, 3) Ageing analysis, 4) Calendar, and 5) Visual Merchandising. This article is written using descriptive analysis method, with support of internal data of Omnilytics and several literature studies. The aim of this article is to provide insights on how Omnilytics works, and its functions for fashion industry players and academics, especially for those who have not understood the use of big data and its concrete benefits. Key words : retail, fashion, data, technology Omnilytics adalah sebuah platform intelegen pasar ritel fesyen yang memberikan informasi menyeluruh menggunakan data dan teknologi seperti: 1) Tolok ukur terhadap kompetitor, 2) Performa tren, 3) Analisa produk berumur, 4) Kalendar, dan 5) Visual merchandising. Artikel ini disusun menggunakan metode analisis deskriptif dari data internal Omnilytics dan studi literatur. Artikel ini bertujuan memberikan paparan mengenai cara kerja Omnilytics dan manfaatnya secara ringkas bagi para pelaku di industri fesyen dan akademisi, terutama bagi yang belum mengenal penggunaan big data dan manfaatnya secara konkrit. Kata Kunci: fesyen, ritel, data, teknologi